The Uighurs Versus the Chinese Government: An Application of Realistic Conflict Theory. Issue 2 (2nd April 2016) - Terhune, Victoria; Matusitz, Jonathan
ABSTRACT: This article applies Realistic Conflict Theory to the understanding of Uighur terrorism against the Chinese in the Xinjiang Uighur Autonomous Region. By and large, Realistic Conflict Theory posits that disagreement over objectives and competition over limited resources tend to lead to intergroup conflict. By the same token, as an "in-group" mentality emerges, a great amount of discrimination and negative stereotypes are the consequences for the out-group. The Uighurs (a Muslim people) have had complicated relations with China, so much so that they were increasingly bent on creating their own independent state. As the People's Republic of China grew more powerful, its stance toward the Uighurs was reflected through a shift from mild hostilities to more acute persecutions. For these reasons, the Uighurs have resorted to terrorism.